DAMPAK KINERJA PERBANKAN SYARIAH (BANK SYARIAH MANDIRI) SETELAH DILANDA PANDEMI COVID 19 - Rosalia Wilda Cahyani; Muhammad Iqbal Fasa; Suharto Suharto (Jurnal Bina Bangsa Ekonomika, 2022)
The Covid-19 pandemic is increasingly spreading to all countries in the world, including Indonesia. all of which are all sectors including the economic sector experiencing contraction as experienced by Islamic banks. However, Islamic banking is categorized as a financial sector that is still able to withstand the storm of the crisis. The purpose of this study is to analyze the banking performance of Bank Syariah Mandiri (BSM) after being hit by the covid-19 pandemic, the method used is a qualitative descriptive method accompanied by a sample of Islamic commercial banks in Indonesia. The secondary data obtained is in the form of data analysis on the development of sharia banking in the creation of COVID-19 based on Third Party Funds (DPK). Source of data for the period January to July 2020 which can be from Islamic bank report data. The results of in-depth research that the performance of Islamic banking based on third party funds (DPK) fluctuated